Pelaksanaan Sistem Pengurusan Sekolah Kualiti (SPSK) di Sekolah Rendah daerah Johor Bahru - Haron, Hairunizad (2012)
Research was conducted to survey the implementation of the Sistem Pengurusan Sekolah Kualiti (SPSK) in Johor Bahru primary schools in terms of level of knowledge and practice of teachers as well as comparison of implementation based on gender. There are 162 survey responses received from teachers who represent the population of 277 teachers in five primary schools. Questionnaire containing 48 items based on the quality model Clarence Burns (1997) and six working procedures of the SPSK. Descriptive statistical techniques and inferential statistical techniques such as mean, frequency, Pearson correlation, t-test and oneway Anova test was used to achieve the research objectives. Three hypotheses were tested at the confidence level P <0.05. As a result of this research has rejected two of the three null hypotheses. Survey results found that the level of knowledge and practice of teachers in this district in implementing the SPSK are high and the level of practice is higher than the level of knowledge. Through t-test, shows that female teachers level of knowledge and practice are higher than male teachers. Hypothesis test results also showed that there were significant differences in level of knowledge between male and female teachers, but there was no significant difference in the level of practice. One way Anova test in this study explain the existence of highly significant differences in the level of implementation of the SPSK between schools of different types and categories further reject the null hypothesis. High Performance Schools is a school of the highest level of implementation in the SPSK followed by Cluster School and three other daily schools. Important implication of this study was gender and different types of school factors play a role in ensuring the implementation of Sistem Pengurusan Sekolah Kualiti (SPSK) in primary schools can be well implemented and achieved quality objectives. Finally some action proposals were made to improve the quality of the implementation of this system at other schools that have not yet implementing SPSK.